Here's the question you clicked on:
a123
Logic Help! Prove: R 1. S -> ~T (premise) 2. T (premise) 3. ~S -> R (premise)
have no fear, amistre the logician is here ! :)
(s -> -t) = (-s -> r) prove this?
Prove that R is a true statement
lol ... first i have to understand the question
what does it mean that everything is a premise ?
That means that they gave us that information in the book, and I have to complete the proof using that information. It's like the "given."
I was asking amistre - what it actually means :)
dunno, i think thats the next chapter in class :)
premise i think means, assume its true
S -> ~T = 1 when S=0 and T = 1, 0; and when S=1 and T=0 T = 1; so S = 0 ~S -> R = 1 -0 -> R = 1 when R = 1
Premise means it is given. It is presumed to be true.
S -> -T 1 -> 0 = 0 1 -> 1 = 1 0 -> 0 = 1 0 -> 1 = 1 T = 1 0 -> 0 = 1 -S -> R 1 -> 0 = 0 1 -> 1 = 1
Thanks. I'll go with this.
i got know idea how to write it out better :)